Synthesis of several bisabolane sesquiterpenoids from xanthorrhizol isolated from C. xanthorrhiza and their bioactivities - Ngai, Mun Hong; Sirat, Hasnah (Penerbit Universiti Sains Malaysia, 2004)
Xanthorrhizol (1) is a bisabolane-type sesquiterpenoid obtained as the main constituent of the rhizome oil of temu lawak, Curcuma xanthorrhiza, which has been utilised as a tonic in Indonesia and as a choleretic drug in Europe. As regards to its bioactivities, it has been shown that xanthorrhizol (1) possessed antifungal activity against Candida albicans (MIC=68.75 μg/mL) and cytotoxic against human nasopharyngeal carcinoma cell line (KB, EC50 = 4.90 μg/mL) (Mata et al., 2001). Although the synthesis of 1 has been extensively studied, the chemistry of this compound has only be studied in a limited extent.